Some classical patterns in John Milton's Latin funerary compositions - Muñoz García de Iturrospe, María Teresa; Ruiz Arzalluz, Iñigo; Martínez Sobrino, Alejandro; Muñoz García de Iturrospe, María Teresa; Ortigosa Egiraun, Iñaki; San Juan Manso, Enara (Vitoria: Universidad del País Vasco, 2014)
En esta aportación abordamos un estudio detallado de las composiciones de tema funerario del corpus poético compuesto en latín por el insigne poeta inglés Milton desde 1626. Las primeras elegías aúnan perfectamente el dístico con el lamento, luctuoso o amoroso, con un profuso y a veces excesivo empleo de circunloquios mitológicos (sus modelos primordiales son Horacio y Ovidio) al que se suman clichés propios de la poesía epigráfica latina y de reminiscencias de las composiciones funerarias y consolatorias de los poetas latinos.
In this contribution we deal with a detailed study of the funerary compositions of the poetical corpus written in Latin since 1612 by the renowned English poet Milton. The first elegies join the distich with the lament, either mourning or love lament, with an abundant and sometimes excessive use of mythological circumlocutions (his main models are Horace and Ovid) to which clichés of the Latin epigraphic poetry are added as well as other reminiscences of classical funerary and consolatory compositions
Keywords: Milton, John, -- 1608-1674; Horacio Flaco, Quinto; Ovidio Nasón, Publio; Literatura latina